BROCCOLI (Brassica oleracea L) ETHANOL EXTRACT: A MOISTURIZER AND ITS EVALUATION IN ASPECTS OF PHYSICAL CHARACTERISTICS - Aldila, Silvy; Puruhita, Ranatri; Uliana, Syahkhirotul Exma; Sa’adah, Anifatus; Gloria, Fransisca (Science and Community Pharmacy Journal, 2024)
Skin disorders that are dry, dull, scaly, and not fresh affect everyone. Moisturizing cream is a cosmetic product that effectively hydrates and improves dry skin. Broccoli, scientifically known as Brassica oleracea L, is rich in vitamin C components, vitamin E (α-tocopherol), and flavonoids, which act as natural antioxidants and provide moisturizing properties for the skin. Producing extracts by the maceration process. Broccoli extract is utilized in the formulation of four moisturizing cream preparation compositions, each with a concentration of F1 (0%), F2 (2%), F3 (3%), and F4 (4%). The moisturizing cream formulation is assessed for its physical properties. Conducting tests to evaluate the dosage characteristics of moisturizing creams, includes organoleptic testing, homogeneity testing, pH testing, dispersion testing, adhesion testing, and viscosity testing. The concentration of broccoli extract in the four moisturizing cream preparation formulations is as follows: F1 (0%), F2 (2%), F3 (3%), and F4 (4%). The moisturizing cream formulation is assessed for its physical properties. Conducting tests to evaluate the dosage properties of moisturizing creams, including sensory evaluation, uniformity assessment, pH measurement, dispersion analysis, adhesion examination, and viscosity measurement